Wielokulturowość w przekładzie Opowieści galicyjskich Andrzeja Stasiuka - Buczek, Marta (Przekłady Literatur Słowiańskich, 2011)
Intercultural dialogue in Slovak translation of Andrzej Stasiuk book Opowieści galicyjskie The article deals with the question of intercultural dialogue in Slovak translation of Andrzej Stasiuk book under the title Opowieści galicyjskie. The author draws attention to translation problems resulting from the peculiarity of origin, in which a dialog of many cultures decides about the inner structure of a text. The author discusses translation problems focuses on text signals, significant structure elements which state the limits of semantic area of the origin. It defines the way of reading and transfering the sense of origin implied in translation. The author considers what extent the translator of Opowieści galicyjskie managed to transfer in translation the aspects of cultures mix up and coexistence.